Impact of a Mobile Health Intervention on Long-term Nonadherence After Lung Transplantation: Follow-up After a Randomized Controlled Trial - Geramita, Emily M. (Transplantation, 2020)
BACKGROUND. In a randomized controlled trial, lung transplant recipients (LTRs) using a mobile health intervention, Pocket Personal Assistant for Tracking Health (Pocket PATH), showed better adherence to the medical regimen than LTRs receiving usual care during the first year posttransplant. We examined whether these effects were maintained beyond the end of the trial and evaluated other potential risk factors for long-term nonadherence. METHODS. Adherence in 8 areas was evaluated at follow-up in separate LTR and family caregiver (collateral) assessments. Pocket PATH and usual care groups’ nonadherence rates were compared; multivariable regression analyses then examined and controlled for other patient characteristics’ associations with nonadherence. RESULTS. One hundred five LTRs (75% of survivors) were assessed (M = 3.9 years post-transplant, SD = 0.8). Nonadherence rates in the past month were 23%–81% for self-care and lifestyle requirements (diet, exercise, blood pressure monitoring, spirometry), 13%–23% for immunosuppressants and other medications, and 4% for tobacco use, with 31% clinic appointment nonadherence in the past year. In multivariable analysis, the Pocket PATH group showed lower risk of nonadherence to lifestyle requirements (diet/exercise) than the usual care group (P < 0.05). Younger age and factors during the first year posttransplant (acute graft rejection, chronically elevated anxiety, less time rehospitalized, nonadherence at the final randomized controlled trial assessment) were each associated with nonadherence in at least 1 area at follow-up (P < 0.05). CONCLUSIONS. Pocket PATH did not have sustained impact on most areas of the regimen, although we identified other risk factors for long-term nonadherence. Future work should explore strategies to facilitate sustained effects of mobile health interventions.